A Case of Fulminant Bacillus cereus Lung Necrosis in a Preterm Neonate. (October 2019) - Viel-Thériault, Isabelle; Saban, Jeremy; Lewis, Alana; Bariciak, Erika; Grynspan, David
Bacillus cereus is a ubiquitous Gram-positive rod seldom considered pathogenic in clinical isolates. However, it possesses multiple virulence factors explaining why it has been linked to fulminant and pyogenic infections in vulnerable hosts. Its recovery from sterile samples in immunocompromised patients cannot be disregarded. Premature infants would fall into this category. We describe the case of a neonate born at 26 weeks of gestational age, who died of a rapidly progressive B. cereus necrotizing pneumonia following suspected nosocomial acquisition. The rapidity of his course and the autopsy findings of necrosis with minimal inflammation suggest a toxin-mediated process. Pathologists should be aware of this pathogen and obtain proper microbiological samples in the presence of such autopsy findings, as the diagnosis may have infection-prevention implications in health-care settings.